Confirmatory Factor Analysis of the Spirituality and Spiritual Care Rating Scale: A Cross-Sectional Study in Eight US Nursing Homes - McEvoy, Sarah (Journal of religion and health, 2024)
The aim of this study was to test a modified Spirituality and Spiritual Care Rating Scale (SSCRS) and report initial findings, based on a cross-sectional descriptive survey from eight nursing homes in the USA. This study examined the psychometric properties of a modified version of the SSCRS for assessing the perceptions of staff (i.e. nurses, rehabilitation staff, food and nutrition service staff, activities staff, social workers, and administrative staff) who work in nursing homes. The modified version of the SSCRS is measuring respondents' perceptions of spirituality, spiritual care, religiosity, and personalized care. Confirmatory factor analysis showed satisfactory goodness of fit for the original four-factor structure of the SSCRS. The modified version demonstrated good internal consistency and reliability (Cronbach's alpha ranging from 0.71 to 0.90). Initial findings showed statistically significant differences across all four sub-scales. Further research is needed to psychometrically test the modified tool.